Antiplasmodial- and chloroquine resistance reversal properties of a new diterpene from Croton steenkampianus - Meyer, J.J.M. (Jacobus Johannes Marion) (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2008.